Treatment of resistant tennis elbow by a novel technique: Platelet-rich plasma injection and drilling of lateral humeral epicondyle - Medhat Tawfik Maaty (Journal of Orthopedics, Traumatology and Rehabilitation, 2018)
Introduction: Tennis elbow is a common disease in orthopedic surgery. Recently, the high-rate outcomes of local injection of platelet-rich plasma (PRP) were reported. This study was conducted to evaluate and compare the results of combining the percutaneous drilling of lateral humeral epicondyle and local injection of PRP for resistant tennis elbow to other more invasive techniques. Patients and Methods: Between January 2014 and December 2015, 25 patients underwent this study. The patients underwent percutaneous drilling of lateral humeral epicondyle and local injection of PRP. Results: The average follow-up time was 18 months (range: 12–27 months). Eighteen patients (72%) were rated as having excellent results, 4 patients (16%) were rated as having good results, and 3 patients (12%) were rated as having a poor result without any improvement. Conclusions: Combining the percutaneous drilling of lateral humeral epicondyle and local PRP injection in tennis elbow improved the results and compared favorably with other techniques.